Cumulative Doses to Brain and Other Critical Structures After Multisession Gamma Knife Stereotactic Radiosurgery for Treatment of Multiple Metastatic Tumors - Yuan, Jianling; Lee, Richard; Dusenbery, Kathryn Ellen; Lee, Chung K.; Mathew, Damien C.; Sperduto, Paul Wayne; Watanabe, Yoichi (Frontiers in Oncology, 2018)
Purpose Repeat stereotactic radiosurgery (SRS) is an attractive alternative to whole brain radiation therapy (WBRT) for treatment of recurrent brain metastases (BM). The purpose of this study is to determine the cumulative doses to the brain and critical normal structures in patients who underwent repeat courses of Gamma Knife (GK) SRS. Materials and methods We retrospectively identified ten patients who received at least three GK-SRS sessions for multiply recurrent BM at our institution from 2013 to 2016. We used Velocity™ 3.1.0 software to co-register the magnetic resonance imaging images and the dose data of all treatment sessions for each patient. The cumulative doses to brain, lenses, eyes, brainstem, optic nerves, chiasm, and hippocampi were calculated. Dose–volume histograms, as well as the mean, median and maximum doses of these structures, were analyzed. Results The median number of SRS was five sessions (range = 3–7 sessions) per patient over a median treatment span of 510 days (112–1,197 days), whereas the median number of metastatic tumors treated per patient was 25.0 (10–63). The median of the total tumor volume was 9.5 cc (2.3–75.9 cc). The median of the mean cumulative dose to the whole brain was 4.1 Gy (1.7–16.4 Gy). The medians of the maximum doses to the critical structures were as follows: brainstem, 6.1 Gy (2.2–28.9 Gy), chiasm, 3.9 Gy (1.8–10.8 Gy), right optic nerve, 2.9 Gy (1.2–9.0 Gy), and left optic nerve, 2.6 Gy (1.0–6.5 Gy). The medians of the mean and maximum cumulative doses to the hippocampi were 3.4 Gy (1.0–14.4 Gy) and 13.8 Gy (1.5–39.3 Gy), respectively. The median survival for the entire cohort was 26.7 months, and no patients developed radiation necrosis. Conclusion Our study demonstrated that multisession GKSRS could be delivered with low cumulative doses to critical normal structures. Further studies are required to fully establish its role as an alternative treatment strategy to WBRT for the treatment of multiply recurrent BM.